Comparative efficiency of rice husk-derived biochar (RHB) and steel slag (SS) on cadmium (Cd) mobility and its uptake by Chinese cabbage in highly contaminated soil. Issue 12 (15th October 2018) - Bashir, Saqib; Salam, Abdus; Chhajro, Muhammad Afzal; Fu, Qingling; Khan, Muhammad Jamal; Zhu, Jun; Shaaban, Muhammad; Kubar, Kashif Ali; Ali, Umeed; Hu, Hongqing
ABSTRACT: Cadmium (Cd) contamination in red soil has been considered as a severe threat due to its toxic effects on plants and food security. This study aims to evaluate the comparative efficiency of rice husk-derived biochar (RHB) and steel slag (SS) metal stabilizer on decreasing Cd mobility and bioavailability to Chinese cabbage grown on acidic contaminated red soil. Several extraction techniques: a sequential extraction procedure, the European Community Bureau of Reference, toxicity characteristics leaching procedure, ammonium nitrate, and simple bioaccessibility extraction test were used to measure Cd mobility after amelioration of the investigated soil. The results indicated that application of stabilizer significantly increased soil chemical properties including soil pH, cation exchange capacity, nutrients, and organic matter. The soluble portion of Cd in soil was significantly decreased by 17.6–31.2% and 7.8–11.7% for RHB and SS at 1.5% and 3% application rate, respectively. Moreover, Cd bioaccessibility was significantly declined by 37.08% with RHB and 11.3% with SS at 3% rate. Inlcorporation of RHB at 3% can effectively immobilize Cd and thereby, reduce its phytoavailability to cabbage in Cd-contaminated soil to mitigate food security risks.